2017
DOI: 10.1371/journal.pone.0182650
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of independent and pleiotropic genetic effects in the metabolic syndrome in a hypertensive rat

Abstract: Hypertension is a major risk factor for cardiovascular disease, Type 2 diabetes, and end organ failure, and is often found concomitant with disorders characteristic of the Metabolic Syndrome (MetS), including obesity, dyslipidemia, and insulin resistance. While the associated features often occur together, the pathway(s) or mechanism(s) linking hypertension in MetS are not well understood. Previous work determined that genetic variation on rat chromosome 17 (RNO17) contributes to several MetS-defining traits (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…) were used including congenic Lyon hypertensive rats with substituted fragments of chromosome 17 (Ma et al. ). These rat strains differ in cardiovascular and metabolic parameters (Vincent et al.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…) were used including congenic Lyon hypertensive rats with substituted fragments of chromosome 17 (Ma et al. ). These rat strains differ in cardiovascular and metabolic parameters (Vincent et al.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the rats were previously used as breeders whose offspring were used for another study (Ma et al. ). The characteristics of the individual animals included in this study are presented in Tables and .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the LH strain is a comprehensive MetS model for both physiological and genetic studies. Comprehensive genetic studies in the LH rat determined that MetS is polygenic, with both independent and pleiotropic genetic effects on MetS traits, and combined fine-mapping and systems genetic studies have identified multiple loci and candidate genes [24,22,[25][26][27][28].…”
Section: Inbred Selection Models Of Metsmentioning
confidence: 99%